THE SOCIAL INNOVATION WHITE BOOK’S DRAFTING PROCESS AND RESULTS - Olajos, István (European Integration Studies, 2022)
This article summarises the work of Definition Working Group of the National Social Innovation Laboratory and the key findings of the resulting White Paper, as a prelude to the evaluation of the Social Innovation Strategy, the second part of the Social Innovation White Paper.